2022
DOI: 10.3390/v14040840
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost and Rapid Method of DNA Extraction from Scaled Fish Blood and Skin Mucus

Abstract: PCR-based DNA amplification has been one of the major methods in aquaculture research for decades, although its use outside the modern laboratory environment is limited due to the relatively complex methods and high costs. To this end, we investigated a swabbing and disc protocol for the collection of DNA samples from fish which could extract DNA from fish skin mucus by a non-invasion technique costing only $0.02 (USD) and requiring less than 30 seconds. The disc method that we chose could use the cheap filter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The results demonstrated that swabs were as effective as organ samples. Mucus swabs were previously used in a Chinese study on crucian carp [45]. A positive result indicated Carassius auratus herpes virus DNA could be detected using the mucus swab sampling method.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that swabs were as effective as organ samples. Mucus swabs were previously used in a Chinese study on crucian carp [45]. A positive result indicated Carassius auratus herpes virus DNA could be detected using the mucus swab sampling method.…”
Section: Discussionmentioning
confidence: 99%
“…CaHV DNA was extracted from the crucian carp infected with CaHV, by using skin mucus swabbing and the disc method as we described before ( Gui et al., 2022 ). Briefly, healthy crucian carp were injected intraperitoneally with diseased fish tissue filtrate (viral suspension) kindly provided by Dr. Qiya Zhang (Institute of Hydrobiology, Chinese Academy of Sciences).…”
Section: Methodsmentioning
confidence: 99%
“…Based on our previous study of the extraction of DNA from fish skin mucus within 30 seconds with low cost (USD $0.02) ( Gui et al., 2022 ), we established a rapid, sensitive and cheap method to detect CaHV within 35min from sample collection to result interpretation. Our study could provide a simple, rapid, and low-cost detecting application for POCT in aquaculture industry.…”
Section: Introductionmentioning
confidence: 99%
“…However, limited advances have been made toward non-lethal pathogen detection in fish, particularly in small-sized ones. The successful detection and isolation of fish viruses obtained from the swabbing of epithelial cells [ 31 , 32 ], as well as the consistent results obtained in amphibians [ 33 ], suggests that this approach may be a reliable method for molecular detection of viral DNA [ 34 ], and an alternative for sampling a threatened species.…”
Section: Introductionmentioning
confidence: 99%